Fry bread : a Native American family story - Maillard, Noble; Martinez-Neal, Juana (New York : Roaring Brook Press, 2019)
As children help a Native American grandmother make fry bread, delves into the history, social ways, foodways, and politics of America's 573 recognized Indian tribes.
Includes bibliographical references.
Keywords: Bread -- Fiction; Indians of North America -- Fiction; United States - Native American - Juvenile Fiction; Cooking & Food; Diversity & Multicultural; Ethnic Orientation; Family life